Hydrodesulfurization of JP-8 fuel and its microchannel distillate using steam reformate - Huang, Xiwen; King, Dale A.; Zheng, Feng; Stenkamp, Victoria S.; TeGrotenhuis, Ward E.; Roberts, Benjamin Q.; King, David L. (Catalysis today, 2008)
A field-deployable process for generation of clean desulfurized fuel from JP-8 feedstock is described. The process employs a compact hydrodesulfurization unit, operated in the vapor phase using steam reformate provided by an integrated steam reformer, as a replacement for hydrogen co-feed gas. The process includes a microchannel distillation unit upstream of the hydrodesulfurizer unit, which allows use of a lighter feed fraction to be processed in place of the full JP-8. The novel microchannel distillation concept is described and performance data for the unit, operating as a rectifier, are provided. Since the generated light fraction fuel from microchannel distillation contains fewer refractory sulfur components, the subsequent HDS process can readily achieve a significant sulfur reduction. The overall process can generate an ultra-clean JP-8 light fraction fuel with approximately 300 ppb sulfur residual. Hydrodesulfurization of full JP-8 fuel without the microchannel distillation unit was also studied. The effect of various operating parameters on the overall hydrodesulfurization performance, as well as the conversion of some individual sulfur components such as 2,3-dimethyl-benzothiophene, 2,3,5-trimethyl-benzothiophene and 2,3,7-trimethyl-benzothiophene, were investigated. Steam content in reformate at 30 mol% or less was found to improve HDS performance compared with dry reformate, despite a decrease in hydrogen partial pressure. However, at even higher concentrations of steam, hydrodesulfurization performance decreased.